The Effect of Attractions, Amenities and Accessibility on Visiting Decisions during the Covid-19 Pandemic in the Malino Area, Gowa Regency - ER Ummi Kalsum; Nurjannah Nurjannah; Violetha Simatupang (Newinera Publisher, 2024)
During the COVID-19 Pandemic, tourists certainly require the protection in minimizing the transmission of the COVID-19 virus during travel activities in the Malino Region, Gowa Regency. With the hope of gaining back the public trusts. As it is believed that tourism activities will be achieved if these activities are equipped with tourist travel facilities. This study aims to analyse the effects of Attraction (X1), Amenity (X2) and Accessibility (X3) on Visiting Decisions (Y) during the COVID- 19 Pandemic in the Malino Region, Gowa Regency. This study uses quantitative methods by processing data obtained from the research location. The population in this study were all respondents who had visited Malino during the COVID-19 pandemic as many as 71,288 people and the number of samples selected was 398 individuals using a research questionnaire as a research instrument which was then processed using SPSS software version 23. From the results of the study, it indicates that the partial test results on Attractions (X1) have a significant effect on Visiting Decisions (Y), Amenity (X2) does not have a significant effect on Visiting Decisions (Y) and Accessibility (X3) has a significant effect on Visiting Decisions (Y) and simultaneous testing that Attractions (X1), Amenity (X2) and Accessibility (X3) have a significant effect on visiting decisions (Y).